Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Motivasi Serta Dampaknya pada Kinerja Pegawai di Dinas Pendidikan Kota Sungai Penuh - Saputra, Alan Yolan; Syeikh, Saiyid; Akbar, Ali (Universitas Batanghari, 2024)
This research is motivated by the success of an institution or organization in achieving its goals inseparable from the role and performance of employees in it. One of the indicators to achieve such success is human resources. This study aims to (1) describe the picture of leadership, work environment, employee motivation and performance (2) know and analyze the influence of leadership and work environment both directly and indirectly on employee motivation (3) know and analyze the influence of leadership and work environment both directly and indirectly on employee performance (4) know and analyze the influence of motivation on employee performance (5) know and analyze influence leadership and work environment through motivation for employee performance at the Sungai Full City Education Office. The results of the study showed (1) leadership and work environment in good condition and motivation and performance of employees at the Sungai Full City Education Office. (2) Leadership and work environment directly and indirectly affect employee motivation at the Sungai Full City Education Office, the value of direct influence is 44.89% and indirect influence is 28.32% so that the total influence is 73.21% and the remaining 26.79% is influenced by other factors. (3) Leadership and work environment directly and indirectly affect the performance of employees at the Sungai Full City Education Office, the value of direct influence is 41.28% and indirect influence is 31.66% so that the total influence is 72.94% and the remaining 27.06% is influenced by other factors. (4) Motivation affects the performance of employees at the Sungai Full City Education Office by 72.59% and the remaining 27.41% is influenced by other factors. (5) Leadership and work environment through motivation have a direct influence of 41.28% and an indirect influence of 34.56% on employee performance so that the overall total influence of leadership and environment through motivation on employee performance is 75.84% at the Sungai Full City Education Office.